2022
DOI: 10.3389/fnagi.2022.823502
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Magnetic Resonance Imaging Reveals Aberrant Brain Age Trajectory During Youth in Schizophrenia Patients

Abstract: Accelerated brain aging had been widely reported in patients with schizophrenia (SZ). However, brain aging trajectories in SZ patients have not been well-documented using three-modal magnetic resonance imaging (MRI) data. In this study, 138 schizophrenia patients and 205 normal controls aged 20–60 were included and multimodal MRI data were acquired for each individual, including structural MRI, resting state-functional MRI and diffusion tensor imaging. The brain age of each participant was estimated by feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 93 publications
0
11
1
Order By: Relevance
“…Chen et al also found that the normalized predicted age difference did not show a significant correlation with the duration of illness in schizophrenia 23 . We found that previous studies had inconsistent results on the association between the brain age gap and duration of illness in individuals with schizophrenia 14 , 17 , 21 , 22 . The relevant studies are still limited.…”
Section: Introductioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Chen et al also found that the normalized predicted age difference did not show a significant correlation with the duration of illness in schizophrenia 23 . We found that previous studies had inconsistent results on the association between the brain age gap and duration of illness in individuals with schizophrenia 14 , 17 , 21 , 22 . The relevant studies are still limited.…”
Section: Introductioncontrasting
confidence: 59%
“…Koutsouleris et al found a linear increase in brain age gap from the at-risk, recent onset, and recurrent stages of individuals with schizophrenia 22 . Huang and colleagues indicated that the brain age gap of young individuals with schizophrenia was larger than that of healthy controls; however, the same result was not observed in middle-aged individuals with schizophrenia 21 . Demro et al demonstrated that the disease course of psychotic illness was not significantly correlated with their brain age gap 14 .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies on brain-age prediction have also demonstrated that individuals with schizophrenia exhibit deviations in brain aging trajectories, as indicated in both T1-weighted magnetic resonance imaging (MRI) [16][17][18][19][20][21][22][23][24] and DTI [25,26] findings. The recent studies used multimodal MRI to evaluate the brain age gap in patients with schizophrenia and obtained results consistent with those of studies using a single neuroimaging modality [27][28][29][30].…”
Section: Introductionmentioning
confidence: 53%